Obesity in Humans Is Characterized by Gut Inflammation as Shown by Pro-Inflammatory Intestinal Macrophage Accumulation - Rohm, Theresa V.; Fuchs, Regula; Müller, Rahel L.; Keller, Lena; Baumann, Zora; Bosch, Angela J. T.; Schneider, Romano; Labes, Danny; Langer, Igor; Pilz, Julia B.; Niess, Jan H.; Delko, Tarik; et al. (Frontiers in Immunology, 2021)
Chronic low-grade inflammation is a hallmark of obesity and associated with cardiovascular complications. However, it remains unclear where this inflammation starts. As the gut is constantly exposed to food, gut microbiota, and metabolites, we hypothesized that mucosal immunity triggers an innate inflammatory response in obesity. We characterized five distinct macrophage subpopulations (P1-P5) along the gastrointestinal tract and blood monocyte subpopulations (classical, non-classical, intermediate), which replenish intestinal macrophages, in non-obese (BMI<27kg/m2) and obese individuals (BMI>32kg/m2). To elucidate factors that potentially trigger gut inflammation, we correlated these subpopulations with cardiovascular risk factors and lifestyle behaviors. In obese individuals, we found higher pro-inflammatory macrophages in the stomach, duodenum, and colon. Intermediate blood monocytes were also increased in obesity, suggesting enhanced recruitment to the gut. We identified unhealthy lifestyle habits as potential triggers of gut and systemic inflammation (i.e., low vegetable intake, high processed meat consumption, sedentary lifestyle). Cardiovascular risk factors other than body weight did not affect the innate immune response. Thus, obesity in humans is characterized by gut inflammation as shown by accumulation of pro-inflammatory intestinal macrophages, potentially via recruited blood monocytes. Understanding gut innate immunity in human obesity might open up new targets for immune-modulatory treatments in metabolic disease.